PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP AUDIT DELAY - LALU PRIYA AJINUGRAHA WARDI (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to examine the influence of audit committee effectiveness on audit delayand focusing on manufacturing companies registred on the Indonesia Stock Exchangein 2017. There are about 69 data were collected using purposive sampling method andwere assessed using the multiple regression analysis method an application namedSPSS. The results of thise study show that the effectiveness of audit committees proxiedby the size of the audit committee, the skill of the audit committee members, and thefrequency of audit committee meetings has been proved to have an influence on auditdelay. The adjusted R-squared value (coefficient of determination) is 0.443 whichmeans that 44.3% of Audit Delay variables will be influenced by the independentvariables and they are, Number of Members (X1), Meeting Frequency (X2), and Skill(X3). Meanwhile the remainder is explained by other variables.Keywords: Audit delay, effectiveness of audit committee, Indonesia Stock Exchange